692 AMV564, a clinically active T cell engager, induces a target-dependent adaptive immune response. (9th November 2020) - Eckard, Sterling; Sarde, Aurelien; Mei, Li; Ruegg, Curtis; Chun, Patrick; Smith, Victoria
Abstract : Background: AMV564 is a potent bispecific T cell engager that binds CD3 and CD33. Due to its bivalent structure, AMV564 is selective for MDSCs via clustered CD33 expressed on the cell surface both in vitro and in patients. MDSCs are responsible for local and systemic suppression of the immune response to both circulating and solid cancers. Targeting MDSC suppression allows T cell priming to be restored in both the lymph nodes and tumor microenvironment, and expands previously activated tumor-specific T cells. Here we report clinical observations and results of our ex vivo assay development. Methods: Cell lines, primary human cells, and patient samples were analyzed using flow cytometry with appropriate marker panels including AMV564 directly labeled (phycoerythrin) or detected with labeled anti-AMV564 antibodies. T cell cytotoxicity assays were conducted using primary human T cells and leukemic blast or other target cells (3:1 ratio) for 48 or 72 hours. Patient peripheral blood was sequenced for TcRbeta CDR3 variable chain on the hsTCRBv4b. Results: AMV564 is currently under investigation in a Phase 1 clinical trial (NCT04128423 ). There have been no dose-limiting toxicities and clinical activity has been observed (RECIST complete response in an ovarian cancer patient) when dosed once daily as a subcutaneous injection. In patients, T cell redistribution is consistent with activation and depletion of both monocytic and granulocytic MDSCs. Immune profile changes consistent with CD8 and Th1 cell activation are observed (figure 1). Furthermore, TCR sequencing data indicate that one cycle of treatment is sufficient to expand and generate de novo clones (figure 2). We developed a primary cell cytotoxicity assay and observe that cytotoxic potency is target dependent. Target cell killing and T cell activation/proliferation depend on CD33 clustering, and both CD4 and CD8 T cells can engage and kill target cells. This is illustrated in assays with KG-1 (M2, clustered) and KG-1a (M0, not clustered) cell lines, in which the KG-1 cells have an EC50 15–20 fold lower than the M0 cell line (figure 3). In addition, there is little to no detectable binding or killing of monocytes or neutrophils, which is consistent with the absence of neutropenia in patients enrolled in the trial to date. Conclusions: AMV564 is a potent conditional T cell agonist which is clinically active. We demonstrate that the combination of T cell activation, increased T cell diversity, and target specificity allow AMV564 to deplete MDSCs and restore a native immune response to cancer. Ethics Approval: This study was approved by the Institutional Review Board (IRB) or Independent Ethics Committee (IEC) at each participating institution.